The Relationship between Cannabis Use Disorders and Social Anxiety Disorder in the National Epidemiological Study of Alcohol and Related Conditions (NESARC) - Buckner, Julia D. (2012)
BACKGROUND: Cannabis use disorders (CUD) are highly comorbid with social anxiety disorder (SAD), and SAD may be a risk factor for cannabis dependence. This study explored these relationships in several ways. First, we examined whether SAD was more likely to be related to cannabis dependence than abuse. Second, we examined the temporal relations between CUD and SAD. Third, we examined whether SAD was related to faster transition from age of first cannabis use to CUD onset relative to other anxiety disorders. Fourth, we tested whether having both disorders was associated with greater impairment and psychiatric comorbidity. METHOD: The sample consisted of adults from Wave 1 of the National Epidemiological Survey on Alcohol and Related Conditions, 2,957 of whom had CUD and no SAD, 1,643 had SAD and no CUD, and 340 had CUD-SAD. RESULTS: SAD was more likely to be related to cannabis dependence than abuse. This relation remained after controlling for race, sex, and some other psychiatric disorders (including some anxiety disorders). Age-of-onset data suggest SAD onset prior to CUD onset for most CUD-SAD respondents. CUD-SAD was related to greater impairment and psychiatric comorbidity than either disorder alone. CONCLUSIONS: Although SAD is related to CUD, it has a stronger association with cannabis dependence than abuse. This link is not better accounted for by other psychopathology measured in this study. SAD onset prior to CUD for the majority of CUD-SAD respondents. Importantly, the co-occurrence of these two disorders appears to result in greater impairment and distress than either disorder alone.